Hidrogéis de poliacrilamida e nanomateriais de carbono funcionalizados para adsorção de corantes catiônicos - Tiago Gonzaga de Oliveira e Silveira (2022)
The widespread use of synthetic dyes in the textile industry promotes a large amount of unused material being discarded in rivers and effluents. However, many of the dyes have a high degree of toxicity, causing the fauna and flora, not only in the aquatic environment, to be largely harmed. Polyacrylamide (PA) hydrogels added with low amounts of oxygenated and aminated carbon nanomaterials (NMC) were developed as adsorbent materials for removing dyes in effluents. NMC were incorporated in three different concentrations, 0.10, 0.25 and 0.50%, during the in-situ polymerization of PA. The nanomaterials were characterized by means of elemental analysis, thermogravimetry, transmission electron microscopy and Zeta potential. The hydrogels were characterized using infrared spectroscopy, thermogravimetry and scanning electron microscopy (SEM). However, only through SEM it was possible to observe changes in the microstructure of the hydrogels, with the incorporation of NMC, such as changes in the porous aspect and decrease in the average diameter of the pores. Zeta potential measurements of the systems containing hydrogel and the dye solution were also performed. Swelling and adsorption capacity studies were carried out in order to evaluate the influence of nanomaterials on these properties. The hydrogels containing CNM demonstrated a great potential of adsorption of malachite green (MG) dye, but they were not efficient for the adsorption of methylene blue and rhodamine 6G dyes. The hydrogel containing 0.25% of graphene oxide (GO) showed a 1500% increase in PA. Even with MG being a cationic dye, a hydrogel containing graphene amines, which showed a positive Zeta potential, obtained similar gains. Hydrogels containing carbon nanotubes (CNT) obtained increases up to 400% in adsorption capacity in relation to the reference. CNT, which are one-dimensional, present a degree of functionalization 3 to 4 times lower than graphene, which are two-dimensional. These results allowed to conclude that the degree of functionalization and dimensionality of the CNM are dominant factors in the adsorption property of MG. Kinetic studies showed that the adsorption of these hydrogels fits the pseudo-second order kinetic model and allowed further discussions on the nature of the physicochemical effects in the MG adsorption process.